2000
DOI: 10.1177/106689690000800206
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Calretinin in Mast Cell Lesions of the Skin

Abstract: The diagnosis of mast cell lesions of the skin can occasionally be challenging. Calretinin, a 29 kD neuron-specific calcium-binding protein found mostly in the CNS and retina, has been shown to be a positive marker for mesotheliomas, and is also expressed in mast cells. We studied the diagnostic value of calretinin and compared our results to other established ancillary studies used to identify mast cells, such as Toluidine blue and the Leder stain. Sixty-three cases were studied, including 45 mast cell lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The first such study was by Sariya et al 155 who, in 2007, reported positive staining for calretinin in 12 (67%) of 18 primary adnexal carcinomas, whereas only 9 (28%) of 32 metastatic adenocarcinomas to the skin were positive for this marker. 11,48,68,142,147 These findings indicate that calretinin, in contrast to S100 protein, another member of the EF-hand family of calcium-binding proteins, is uncommonly expressed in these tumors. This is in contrast to a more recent study by Mahalingam et al 156 who were able to demonstrate calretinin positivity in only 8 (14%) of 59 primary adnexal carcinomas and 5 (10%) of 50 metastatic adenocarcinomas to the skin.…”
Section: Calretinin Expression In Skin Tumorsmentioning
confidence: 95%
See 2 more Smart Citations
“…The first such study was by Sariya et al 155 who, in 2007, reported positive staining for calretinin in 12 (67%) of 18 primary adnexal carcinomas, whereas only 9 (28%) of 32 metastatic adenocarcinomas to the skin were positive for this marker. 11,48,68,142,147 These findings indicate that calretinin, in contrast to S100 protein, another member of the EF-hand family of calcium-binding proteins, is uncommonly expressed in these tumors. This is in contrast to a more recent study by Mahalingam et al 156 who were able to demonstrate calretinin positivity in only 8 (14%) of 59 primary adnexal carcinomas and 5 (10%) of 50 metastatic adenocarcinomas to the skin.…”
Section: Calretinin Expression In Skin Tumorsmentioning
confidence: 95%
“…Among benign soft-tissue tumors, calretinin has been reported to be frequently expressed in lipomas (100%), myxolipomas (100%), spindle cell lipomas (75%), 68 Schwannomas (75% to 100%), 67,68,146 and granular cell tumors (93% to 100%). 11,67,147 It has also been reported, but with less frequency, in proliferative fasciitis (50%), 66 nodular fasciitis (23%), 66 benign fibrous histiocytoma (33%), 66 leiomyoma (0% to 27%), 11,54,55 and solitary fibrous tumor (0% to 13%). 11,61,66,148 Because calretinin is commonly expressed in Schwannomas, but not neurofibromas, some authors have suggested that positivity for this marker favors a diagnosis of Schwannoma over neurofibroma in those instances in which the differential diagnosis is difficult.…”
Section: Calretinin Expression In Soft-tissue Tumorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Anticalretinin stained slides were evaluated for the extent (expressed as an approximate percentage of positive cells) and distribution of specific staining. Intralesional mast cells, known to be calretinin positive [4,5,24,25], were commonly observed but not scored in the analysis. In several sarcomas, scattered reactive-appearing cells were identified by calretinin staining.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…5,9 Calretinin has been also reported to be expressed in mast cells and related lesions. 5,10 In the largest tissue microarray analysis of more than 5,000 samples, calretinin expression was detected in small number of tumors from skin (including squamous and basal cell carcinomas, malignant melanoma, and Merkel cell carcinoma), lung (most commonly small cell carcinoma followed by squamous cell carcinoma), digestive (salivary gland tumors, stomach, small and large intestine adenocarcinomas) and genitourinary tract (most commonly testicular Leydig cell tumor and bladder small cell carcinoma), brain, soft tissues (largely in granular cell tumors and leiomyoblastomas), and neuroendocrine tumors (adrenal cortical adenomas, appendiceal carcinoid, and medullary carcinoma of the thyroid). 9…”
mentioning
confidence: 99%